Acid-excited lithium slag-based cementing material and preparation method thereof

The silicon oxygen and silicon aluminum structures of lithium slag are destroyed through the acid excitation process to generate hydration products, solving the problems of limited effects of traditional alkali excitation technology and the possibility of inducing alkali aggregate reactions, and improving the hydration activity and mechanical properties of lithium slag-based gelling materials.

CN119683879APending Publication Date: 2025-03-25FENGCHENG JIULING LITHIUM IND CO LTD

Patent Information

Application Number
CN202411706785.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The alkali excitation technology of traditional lithium slag-based gelling materials has limited effect and may induce alkali aggregate reactions, affecting the performance and service life of the material.

Method used

The acid excitation process is used to mix lithium slag with mixed acid solution and excite it, destroying the silicon oxygen structure and silicon aluminum structure of the lithium slag, forming hydration products, and improving the hydration activity of the material.

Benefits of technology

The hydration activity of lithium slag-based gelling materials is improved, the risk of alkali aggregate reaction is avoided, the cost is reduced, and the stability of the excitation effect and the mechanical properties of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683879A_ABST
    Figure CN119683879A_ABST
Patent Text Reader

Abstract

The invention provides an acid-excited lithium slag-based cementing material and a preparation method thereof.The preparation method of the acid-excited lithium slag-based cementing material comprises the steps that lithium slag and mixed acid liquor are evenly mixed, and excitation is conducted for a preset time length; wherein the mixed acid liquor comprises one or more of sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, formic acid, acetic acid, propionic acid and oxalic acid; filtering to obtain acid-excited lithium slag, and drying to obtain dry lithium slag; the dry lithium slag and auxiliary materials are mixed and ground to a preset specific surface area, and the lithium slag-based cementing material is prepared. The strong acid is utilized to quickly destroy the silicon-oxygen structure and the silicon-aluminum structure of the lithium slag, so that the strong acid is in contact with water to generate a hydration product, and the hydration activity of the lithium slag-based cementing material is improved. The risk of alkali aggregate reaction is avoided, and the cost is reduced; moreover, acid excitation is carried out at the raw material end, so that the excitation effect is more stable than that of use end excitation of alkali excitation. Therefore, the stability of the excitation effect and the mechanical property of the material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid waste recycling, and in particular to an acid-activated lithium slag-based gelling material and a preparation method thereof. Background Art

[0002] Lithium is an emerging material that is currently developing rapidly. With the large-scale mining and smelting of lithium ore, a large amount of by-products, such as lithium slag, are inevitably produced.

[0003] Lithium slag can be converted into lithium slag-based cementitious materials. The application of lithium slag-based cementitious materials can not only effectively broaden the selection range of building materials, but also play an important role in energy conservation, emission reduction and resource recycling.

[0004] Alkali activation technology is commonly used in the process of preparing lithium slag-based cementitious materials from traditional lithium slag, but its activation effect is relatively limited and may induce alkali-aggregate reaction in some cases, which will have an adverse effect on the performance and service life of the material. Summary of the invention

[0005] The present application provides a rainproof device, a cabinet assembly, an energy storage device and a system that are helpful in reducing the possibility of rainwater entering the interior of a cabinet.

[0006] In a first aspect, an embodiment of the present application provides a method for preparing an acid-activated lithium slag-based gelling material, the method comprising:

[0007] The lithium slag is mixed with a mixed acid solution and excited for a preset time; wherein the mixed acid solution includes one or more of sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, formic acid, acetic acid, propionic acid, and oxalic acid;

[0008] filtering to obtain the acid-activated lithium slag, and drying the same to obtain dry lithium slag;

[0009] The dry lithium slag is mixed with auxiliary materials and ground to a preset specific surface area to obtain a lithium slag-based gelling material.

[0010] According to the first aspect, in a possible implementation manner, the concentration of the mixed acid solution is 5%-70%.

[0011] According to the first aspect, in a possible implementation, in the step of uniformly mixing the lithium slag and the mixed acid solution and stimulating for a preset time, the effective component of the mixed acid is 1%-10% of the mass of the lithium slag.

[0012] According to the first aspect, in a possible implementation manner, in the step of uniformly mixing the lithium slag and the mixed acid solution and stimulating for a preset time, the stimulating time is 1 hour to 24 hours.

[0013] According to the first aspect, in a possible implementation, the specific surface area of ​​the lithium slag-based gelling material is 350-700 cm 2 / g.

[0014] According to the first aspect, in a possible implementation manner, the auxiliary material includes one or more of water-quenched slag powder, fly ash powder, steel slag powder, desulfurized gypsum powder, and slaked lime powder.

[0015] According to the first aspect, in a possible implementation manner, the content of lithium slag in the lithium slag-based gelling material is 10%-70%.

[0016] According to the first aspect, in a possible implementation, the lithium slag-based cementitious material includes: 50 parts of fine lithium slag, 30 parts of water-quenched slag powder, 10 parts of fly ash, 5 parts of desulfurized gypsum powder, and 5 parts of slaked lime powder.

[0017] In a second aspect, the present application also provides an acid-activated lithium slag-based gelling material, wherein the activated lithium slag-based gelling material is prepared by the method for preparing the acid-activated lithium slag-based gelling material according to the first aspect.

[0018] The acid-activated lithium slag-based cementitious material and preparation method thereof provided in the present application use strong acid to quickly destroy the silicon-oxygen structure and silicon-aluminum structure of the lithium slag. These destroyed structures quickly dissolve in water when in contact with water and generate hydration products, thereby improving the hydration activity of the lithium slag-based cementitious material. This method not only avoids the risk of alkali-aggregate reaction and reduces costs; and in the present invention, the acid activation is activated at the raw material end, which is more stable than the activation at the use end of alkali activation. Thus, the stability of the activation effect and the mechanical properties of the material are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0020] Figure 1 The present invention is a schematic flow diagram of a method for preparing an acid-activated lithium slag-based gelling material in an embodiment. DETAILED DESCRIPTION

[0021] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0022] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0024] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0025] The present invention provides a method for preparing an acid-activated lithium slag-based gelling material. Figure 1 As shown, the method comprises the following steps:

[0026] Step S10, mixing the lithium slag and the mixed acid solution evenly, and exciting for a preset time;

[0027] Wherein, the mixed acid solution includes one or more of sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, formic acid, acetic acid, propionic acid, and oxalic acid;

[0028] Step S20, filtering to obtain the acid-excited lithium slag, and drying to obtain dry lithium slag;

[0029] Step S30: Mix the dry lithium slag with auxiliary materials, and grind them to a preset specific surface area to obtain a lithium slag-based gelling material.

[0030] The present invention uses an acid excitation process to rapidly destroy the silicon-oxygen structure and silicon-aluminum structure of lithium slag using a strong acid. These destroyed structures rapidly dissolve into water when in contact with water and generate hydration products, thereby improving the hydration activity of lithium slag-based cementitious materials. This method not only avoids the risk of alkali-aggregate reaction and reduces costs; and in the present invention, the acid excitation is at the raw material end, which is more stable than the use end excitation of alkali excitation. Thus, the stability of the excitation effect and the mechanical properties of the material are improved.

[0031] Specifically, the method comprises the following steps:

[0032] Step S10, mixing the lithium slag and the mixed acid solution evenly, and exciting for a preset time;

[0033] The lithium slag may be lepidolite smelting slag or spodumene smelting slag.

[0034] The mixed acid solution is composed of one or more of sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, formic acid, acetic acid, propionic acid and oxalic acid. These acid substances can quickly destroy the silicon-oxygen structure and silicon-aluminum structure of lithium slag, thereby stimulating the potential hydration activity of lithium slag.

[0035] As the raw material for preparing lithium slag-based cementitious materials, the chemical and physical properties of lithium slag have an important influence on the performance of the final product. The concentration of the mixed acid solution needs to match the properties of the lithium slag to ensure the smooth progress of the acid excitation process. Too low a concentration may not effectively destroy the silicon-oxygen structure and silicon-aluminum structure in the lithium slag, while too high a concentration may cause excessive corrosion, generate unnecessary waste, and increase production costs. In this embodiment, the concentration of the mixed acid solution can be between 5% and 70%, and the selection of the specific concentration needs to comprehensively consider factors such as the properties of the lithium slag, the required excitation effect, and the production cost.

[0036] If the ratio of the effective component of the mixed acid is too low, the silicon-oxygen structure and silicon-aluminum structure in the lithium slag may not be fully destroyed, resulting in poor excitation effect. On the contrary, if the ratio is too high, although the excitation effect may be improved, the amount of acid used will also increase, thereby increasing production costs. In this embodiment, the effective component of the mixed acid (i.e., the part that can participate in the reaction and excite the activity of the lithium slag) can be 1%-10% of the mass of the lithium slag. This ratio ensures the adequacy and economy of the acid excitation effect.

[0037] During the mixing and excitation steps, it is necessary to ensure that the lithium slag and the mixed acid are fully and evenly mixed. If the concentration of the lithium slag and the mixed acid is too high or too low locally, it will directly lead to uneven excitation effects. In areas where the concentration is too high, the lithium slag may be affected by excessive corrosion, while in areas where the concentration is too low, the expected effect may not be achieved due to insufficient excitation. In order to ensure the uniformity of the mixing of the lithium slag and the mixed acid, mechanical stirring, ball milling, air flow stirring, etc. can be used.

[0038] In the preparation process of acid-activated lithium slag-based cementitious materials, the setting of activation time is a crucial link. The length of this time is usually between 1 hour and 24 hours, depending on the type and concentration of the mixed acid and the properties of the lithium slag.

[0039] In actual operation, in order to obtain the best excitation effect, we need to flexibly adjust the excitation time according to the specific situation. Different types and concentrations of mixed acids, as well as the inherent properties of lithium slag, will have a significant impact on the excitation process.

[0040] During the excitation process, the silicon-oxygen structure and silicon-aluminum structure of lithium slag are gradually destroyed under the action of acid. This destructive effect not only changes the microstructure of lithium slag, but also prompts it to generate new substances with hydration activity. These newly generated hydration active substances will play a key role in the subsequent preparation process. They will interact with other components to form lithium slag-based cementitious materials with excellent performance.

[0041] Step S20, filtering to obtain the acid-excited lithium slag, and drying to obtain dry lithium slag;

[0042] After the acid excitation step, the lithium slag and the mixed acid solution fully react to form a substance with hydration activity. At this time, it is necessary to separate the reacted lithium slag from the mixed solution by filtering. The filtration process can use appropriate filtering equipment, such as a filter screen or filter cloth, to ensure the complete separation of the lithium slag and the acid solution.

[0043] The main purpose of drying is to remove excess moisture from lithium slag and improve its dryness. This is not only beneficial for subsequent processing steps such as crushing and grading, but also ensures the stability of lithium slag during storage and transportation.

[0044] Hot air drying, steam drying, solar energy drying and other methods can be used. In actual operation, the appropriate drying method should be selected based on factors such as production scale, cost budget and environmental protection requirements.

[0045] After drying, the excess water in the lithium slag is effectively removed, and dry lithium slag is obtained. Dry lithium slag has higher stability and activity, providing a good basis for the subsequent preparation of lithium slag-based cementitious materials.

[0046] Step S30: Mix the dry lithium slag with auxiliary materials, and grind them to a preset specific surface area to obtain a lithium slag-based gelling material.

[0047] The auxiliary materials include one or more of water-quenched slag powder, fly ash powder, steel slag powder, desulfurized gypsum powder and slaked lime powder. These auxiliary materials can improve the performance of lithium slag-based cementitious materials, such as increasing strength and durability.

[0048] According to the required performance of lithium slag-based cementitious materials, the ratio of dry lithium slag to various auxiliary materials is determined. For example, a typical ratio is: 50 parts of fine lithium slag, 30 parts of water-quenched slag powder, 10 parts of fly ash, 5 parts of desulfurized gypsum powder, and 5 parts of slaked lime powder.

[0049] The content of lithium slag in lithium slag-based cementitious materials is usually 10%-70%, and the specific content needs to be adjusted according to actual needs.

[0050] Mix the dry lithium slag with the selected auxiliary materials according to the determined ratio. During the mixing process, ensure that the various raw materials are evenly distributed to avoid local concentrations that are too high or too low.

[0051] Grind the mixed raw materials to a preset specific surface area, usually 350-700cm 2 / g. Grinding can improve the fineness and activity of raw materials, which is beneficial to the full reaction between the components and the improvement of performance in the subsequent preparation process.

[0052] Ball mills, vertical mills and other grinding equipment can be used for grinding operations. The selection of equipment should be based on comprehensive considerations of factors such as the nature of the raw materials, production scale and the required grinding fineness.

[0053] After mixing and grinding, lithium slag-based cementitious materials can be obtained. This material has excellent properties, such as high strength, high durability, good workability, etc., and can be widely used in engineering fields such as construction, roads, bridges, etc.

[0054] In a second aspect, the present application further provides an acid-activated lithium slag-based gelling material, wherein the acid-activated lithium slag-based gelling material is prepared by the above-mentioned method for preparing the acid-activated lithium slag-based gelling material.

[0055] In the preparation process of acid-activated lithium slag-based cementitious materials, the potential hydration activity of lithium slag is activated by the acid activation process of lithium slag, and the acid substances can quickly destroy the silicon-oxygen structure and silicon-aluminum structure of lithium slag. These destroyed structures are quickly dissolved in water when in contact with water, and hydration products are generated, thereby improving the hydration activity of lithium slag-based cementitious materials. By activating the activity of lithium slag with strong acid, the risk of alkali-aggregate reaction that may be caused by alkali activation can be effectively avoided. In addition, the present invention performs acid activation at the raw material end, which is more stable than the activation at the use end of alkali activation, and the activation effect is more stable.

[0056] In the first embodiment, the preparation process of the acid-activated lithium slag-based gelling material is as follows:

[0057] Take 100 parts of lithium slag, 2 parts of concentrated sulfuric acid, 0.5 parts of phosphoric acid, and 7.5 parts of water.

[0058] Pour 2 parts of concentrated sulfuric acid into 7.5 parts of water and mix well, then pour in 0.5 parts of phosphoric acid and mix well again to obtain a mixed acid solution.

[0059] The mixed acid solution was sprayed into 100 parts of lithium slag and stirred evenly. After stirring evenly, it was placed for 12 hours to obtain acid-activated lithium slag. The activated lithium slag was sent to a vertical mill for drying and grinding to obtain a specific surface area of ​​500 cm 2 / g of ground lithium slag.

[0060] Take 50 parts of ground lithium slag, 30 parts of water-quenched slag powder, 10 parts of fly ash, 5 parts of desulfurized gypsum powder and 5 parts of slaked lime powder and mix them evenly to obtain an acid-activated lithium slag-based cementitious material.

[0061] The mechanical properties of acid-activated lithium slag-based cementitious materials are as follows:

[0062] 3-day mortar strength 7-day mortar strength 28-day mortar strength 14.5MPa 35.9MPa 46.3MPa

[0063] In the second embodiment, the preparation process of the acid-activated lithium slag-based gelling material is as follows:

[0064] Take 98 parts of lithium slag, 5 parts of concentrated sulfuric acid, 2 parts of nitric acid, and 8 parts of water.

[0065] Pour 5 parts of concentrated sulfuric acid into 8 parts of water and mix well, then pour in 2 parts of nitric acid and mix well again to obtain a mixed acid solution.

[0066] The mixed acid solution was sprayed into 98 parts of lithium slag and stirred evenly. After stirring evenly, it was placed for 6 hours to obtain acid-activated lithium slag. The activated lithium slag was sent to a vertical mill for drying and grinding to obtain a specific surface area of ​​600 cm 2 / g of ground lithium slag.

[0067] Take 40 parts of ground lithium slag, 50 parts of water-quenched slag powder, 10 parts of steel slag, 2 parts of desulfurized gypsum powder and 6 parts of slaked lime powder and mix them evenly to obtain an acid-activated lithium slag-based cementitious material.

[0068] The mechanical properties of acid-activated lithium slag-based cementitious materials are as follows:

[0069] 3-day mortar strength 7-day mortar strength 28-day mortar strength 18.5MPa 37.7MPa 49.2MPa

[0070] In the third embodiment, the preparation process of the acid-activated lithium slag-based gelling material is as follows:

[0071] Take 105 parts of lithium slag, 4 parts of concentrated sulfuric acid, 1 part of phosphoric acid, 1 part of oxalic acid, and 9 parts of water.

[0072] Pour 9 parts of concentrated sulfuric acid into 7.5 parts of water and mix well, then pour in 0.5 parts of phosphoric acid and mix well again to obtain a mixed acid solution.

[0073] The mixed acid solution was sprayed into 105 parts of lithium slag and stirred evenly, and then placed for 10 hours to obtain acid-activated lithium slag. The activated lithium slag was sent to a vertical mill for drying and powder grinding to obtain fine lithium slag with a specific surface area of ​​650 cm2 / g.

[0074] Take 50 parts of ground lithium slag, 30 parts of water-quenched slag powder, 10 parts of fly ash, 5 parts of desulfurized gypsum powder and 5 parts of slaked lime powder and mix them evenly to obtain an acid-activated lithium slag-based cementitious material.

[0075] The mechanical properties of acid-activated lithium slag-based cementitious materials are as follows:

[0076] 3-day mortar strength 7-day mortar strength 28-day mortar strength 15.9MPa 37.1MPa 48.8MPa

[0077] In the fourth embodiment, the preparation process of the acid-activated lithium slag-based gelling material is as follows:

[0078] Take 105 parts of lithium slag, 4 parts of oxalic acid, 1 part of phosphoric acid, 1 part of formic acid, and 10 parts of water.

[0079] Pour 4 parts of oxalic acid into 10 parts of water and mix evenly, then pour in 1 part of phosphoric acid and 1 part of formic acid and mix evenly again to obtain a mixed acid solution.

[0080] The mixed acid solution was sprayed into 105 parts of lithium slag and stirred evenly. After stirring evenly, the mixture was placed for 20 hours to obtain acid-activated lithium slag. The activated lithium slag was sent to a dryer for drying, and the dried lithium slag was sent to a ball mill for grinding to obtain a specific surface area of ​​550cm 2 / g of ground lithium slag.

[0081] Take 50 parts of ground lithium slag, 30 parts of water-quenched slag powder, 10 parts of fly ash, 5 parts of desulfurized gypsum powder and 5 parts of slaked lime powder and mix them evenly to obtain an acid-activated lithium slag-based cementitious material.

[0082] The mechanical properties of acid-activated lithium slag-based cementitious materials are as follows:

[0083] 3-day mortar strength 7-day mortar strength 28-day mortar strength 13.7MPa 33.1MPa 44.1MPa

[0084] In the fifth embodiment, the preparation process of the acid-activated lithium slag-based gelling material is as follows:

[0085] Take 90 parts of lithium slag, 4 parts of concentrated sulfuric acid, 4 parts of phosphoric acid, 1 part of formic acid, 1 part of acetic acid, and 9 parts of water.

[0086] Pour 4 parts of concentrated sulfuric acid into 9 parts of water and mix well, then pour in 1 part of phosphoric acid, 1 part of formic acid and 1 part of acetic acid and mix well again to obtain a mixed acid solution.

[0087] The mixed acid solution was sprayed into 90 parts of lithium slag and stirred evenly. After stirring evenly, the mixture was placed for 1 hour to obtain acid-activated lithium slag. The activated lithium slag was sent to a dryer for drying, and the dried lithium slag was sent to a ball mill for grinding to obtain a specific surface area of ​​350cm 2 / g of ground lithium slag.

[0088] Take 50 parts of ground lithium slag, 30 parts of water-quenched slag powder, 10 parts of fly ash, 5 parts of desulfurized gypsum powder and 5 parts of slaked lime powder and mix them evenly to obtain an acid-activated lithium slag-based cementitious material.

[0089] The mechanical properties of acid-activated lithium slag-based cementitious materials are as follows:

[0090] 3-day mortar strength 7-day mortar strength 28-day mortar strength 12.5MPa 31.1MPa 43.4MPa

[0091] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the method of the present invention, addition of auxiliary steps, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an acid-activated lithium slag-based gelling material, characterized in that: The method comprises: The lithium slag is mixed with a mixed acid solution and excited for a preset time; wherein the mixed acid solution includes one or more of sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, formic acid, acetic acid, propionic acid, and oxalic acid; filtering to obtain the acid-activated lithium slag, and drying the same to obtain dry lithium slag; The dry lithium slag is mixed with auxiliary materials and ground to a preset specific surface area to obtain a lithium slag-based gelling material.

2. The method for preparing the acid-activated lithium slag-based gelling material according to claim 1, characterized in that: The concentration of the mixed acid solution is 5%-70%.

3. The method for preparing the acid-activated lithium slag-based gelling material according to claim 1, characterized in that: In the step of uniformly mixing the lithium slag and the mixed acid solution and stimulating for a preset time, the effective component of the mixed acid solution is 1%-10% of the mass of the lithium slag.

4. The method for preparing the acid-activated lithium slag-based gelling material according to claim 1, characterized in that: In the step of uniformly mixing the lithium slag and the mixed acid solution and stimulating for a preset time, the stimulating time is 1 hour to 24 hours.

5. The method for preparing the acid-activated lithium slag-based gelling material according to claim 1, characterized in that: The specific surface area of ​​the lithium slag-based gelling material is 350 cm 2 / g to 700cm 2 / g.

6. The method for preparing the acid-activated lithium slag-based gelling material according to claim 1, characterized in that: The auxiliary materials include one or more of water-quenched slag powder, fly ash powder, steel slag powder, desulfurized gypsum powder and slaked lime powder.

7. The method for preparing the acid-activated lithium slag-based gelling material according to claim 6, characterized in that: The content of lithium slag in the lithium slag-based gelling material is 10%-70%.

8. The method for preparing the acid-activated lithium slag-based gelling material according to claim 6, characterized in that: The lithium slag-based cementitious material comprises: 50 parts of fine lithium slag, 30 parts of water-quenched slag powder, 10 parts of fly ash, 5 parts of desulfurized gypsum powder, and 5 parts of slaked lime powder.

9. An acid-activated lithium slag-based gelling material, characterized in that: The activated lithium slag-based cementitious material is prepared by the method for preparing the acid-activated lithium slag-based cementitious material according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Material and treatment method for passivating sulfur-containing tailing slag and inhibiting sulfur-containing tailing slag from generating acid mine wastewater

    CN115634913A

  • All-solid waste cementing material containing lithium slag and preparation method of all-solid waste cementing material

    CN118344033A

  • Lithium slag-based alkali-activated cementing material as well as preparation method and application thereof

    CN118745085A

  • Refractory mortar based on vacuum aluminothermic reduction lithium slag and preparation method thereof

    CN118878258A

  • Lithium slag-based geopolymer cementing material and preparation method thereof

    CN118955018A

Cited By

  • Acid-excited steel slag-based geopolymer and preparation method thereof

    CN120172666A

  • Composite activator based on lithium slag as well as preparation method and application of composite activator

    CN120647233A